15+3X-11=10-16-5x

Simple and best practice solution for 15+3X-11=10-16-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15+3X-11=10-16-5x equation:


Simplifying
15 + 3X + -11 = 10 + -16 + -5x

Reorder the terms:
15 + -11 + 3X = 10 + -16 + -5x

Combine like terms: 15 + -11 = 4
4 + 3X = 10 + -16 + -5x

Combine like terms: 10 + -16 = -6
4 + 3X = -6 + -5x

Solving
4 + 3X = -6 + -5x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 3X = -6 + -4 + -5x

Combine like terms: 4 + -4 = 0
0 + 3X = -6 + -4 + -5x
3X = -6 + -4 + -5x

Combine like terms: -6 + -4 = -10
3X = -10 + -5x

Divide each side by '3'.
X = -3.333333333 + -1.666666667x

Simplifying
X = -3.333333333 + -1.666666667x

See similar equations:

| x^3-x^2-3x+30000=0 | | 3(12-3y^2)= | | -30+5x=6x+.2 | | 2x-5y+7x-3y= | | 6y^2+1=5y | | (x^4-2x^2+2)*(x^2-2x+3)= | | 2Xsquared+7Xsquared-10=5 | | 6x-5x+8=11 | | (z-2y+2)*(y-2x+3)= | | 2-20=-8 | | 13-2x=27 | | (2x+y-2z)(2x-y+2z)= | | 1125-75d=450 | | m-75=55 | | 10ax-2ax+12x-2a+-2x=0 | | -2(xsquared-6)=-38 | | T=42+6p | | 10ax-2ax+12x-2a+12x=0 | | 5x-6=7x-30 | | 65-10m=3m | | 2sin^2x-3sinx-1=0 | | 2r=1.5r+45 | | -3v+17=-5(v-5) | | 8x-15X=-12 | | 4x+8x-(6x+7)= | | y=2000+.8(y) | | (x+y)(x+z)-(x-y)(x-z)= | | X(5)2=30 | | y=1500+.8(y) | | b(5)/2=30 | | (6)x=2x-28 | | p(x)=[x-(3+3I)][x-(3-3I)](x+1)(x-2) |

Equations solver categories